2016
DOI: 10.1155/2016/7434692
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant Effect of Angelica sinensis Extracts on Chronic Unpredictable Mild Stress‐Induced Depression Is Mediated via the Upregulation of the BDNF Signaling Pathway in Rats

Abstract: Angelica sinensis (AS), a traditional Chinese herbal medicine, has pharmaceutical effects on menstrual illness, cerebrovascular diseases, cardiovascular diseases, and cognitive impairments. However, until recently, few studies had explored its antidepressant effect. The current study attempts to investigate the effect of AS extracts on chronic unpredictable mild stress- (CUMS-) induced depression in rats. Male SD rats were exposed to a CUMS-inducing procedure for 5 weeks, resulting in rodent depressive behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…It has been reported that the level of BDNF is decreased in the hippocampus of type 2 diabetic rats . Elevated expression of BDNF in the hippocampus contributes to the antidepressant‐like effect of Angelica sinensis extracts on CUMS‐induced rats . Meanwhile, it has been confirmed that activation of the TrkB receptor contributes to the therapeutic actions of antidepressant drugs .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been reported that the level of BDNF is decreased in the hippocampus of type 2 diabetic rats . Elevated expression of BDNF in the hippocampus contributes to the antidepressant‐like effect of Angelica sinensis extracts on CUMS‐induced rats . Meanwhile, it has been confirmed that activation of the TrkB receptor contributes to the therapeutic actions of antidepressant drugs .…”
Section: Discussionmentioning
confidence: 94%
“…30 Elevated expression of BDNF in the hippocampus contributes to the antidepressant-like effect of Angelica sinensis extracts on CUMS-induced rats. 31 Meanwhile, it has been confirmed that activation of the TrkB receptor contributes to the therapeutic actions of antidepressant drugs. 32,33 In the present work, we found that NaHS increased the expression levels of BDNF and p-TrkB in the hippocampus of STZ-induced diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…What we do know from preclinical data for Angelica, that may be relevant to CPPD treatment, includes a potential for anti‐inflammatory activity, 11 for reducing stress or depression via a brain neurotrophic factor, for normalising blood cell profiles, as a progesterone antagonist reducing heavy bleeding and to alter mood and relax muscles through γ‐aminobutyric acid (GABA)minergic and serotonergic receptor sites . Putative phytoestrogenic activity may also mimic reproductive hormone therapy .…”
Section: Angelica Sinensis Paeonia Lactiflora and Actaea Racemosamentioning
confidence: 99%
“…Putative phytoestrogenic activity may also mimic reproductive hormone therapy . However, Angelica 's anticoagulant properties contra‐indicate its use in heavy periods . As for Paeonia , it has been shown to have potential antidepressant activity, raising serotonin and dopamine levels, through inhibition of monoamine oxidase activity and it may also relieve dysmenorrhoea through analgesic and anti‐inflammatory properties, inhibiting both leukotriene B4 and prostaglandin E2 production …”
Section: Angelica Sinensis Paeonia Lactiflora and Actaea Racemosamentioning
confidence: 99%
“…Following all testing experiments, blood (0.8-1.0 ml) was obtained from the caudal vein of each rat. Rats were then sacrificed, and the hypothalamus was collected (19), weighed and stored at -80˚C for further experiments.…”
Section: Meps Preparationmentioning
confidence: 99%